2021
DOI: 10.3390/ma14164622
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Ester-Ether Copolymerization Thixo-Tropic Superplasticizer and Nano-Clay on the Buildability of 3D Printable Cementitious Materials

Abstract: The shape retention ability of materials deposited layer by layer is called buildability, which is an indispensable performance parameter for successful 3D printable cementitious materials (3DPC). This study investigated the synergistic effect of nano-clay (NC) and thixotropic superplasticizer (TP) on the buildability of 3DPC. The rheological parameters and static yield stress are characterized by the rheology testing, the green strength is measured by a self-made pressure tester, and the fluidity is tested by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This was similarly confirmed by Quanji et al (2014) [114]. In this field, Wang et al (2021) [119] reported that using nano attapulgite clay increases the static yield stress in 3D printable cementitious materials, warranting the strength improvement essential by the buildability of materials. As shown in Figure 7, Liu et al (2018) [120] confirmed these observations and showed that using nano-clay, as a viscosity modifier, significantly improves the plastic viscosity and yield stress of paste, especially for a lower w/c.…”
Section: Effect Of Clays On Viscosity Of Concretementioning
confidence: 65%
“…This was similarly confirmed by Quanji et al (2014) [114]. In this field, Wang et al (2021) [119] reported that using nano attapulgite clay increases the static yield stress in 3D printable cementitious materials, warranting the strength improvement essential by the buildability of materials. As shown in Figure 7, Liu et al (2018) [120] confirmed these observations and showed that using nano-clay, as a viscosity modifier, significantly improves the plastic viscosity and yield stress of paste, especially for a lower w/c.…”
Section: Effect Of Clays On Viscosity Of Concretementioning
confidence: 65%
“…The morphology of the ANC deposit was examined with the aid of the SEM technique and such observations were performed directly on the fiber surface after the nanoclay-based conditioning and drying of WCF bundles. From Figure 8, the first noticeable feature is the uniform nanoceramic coating along the entire length of the fibers, showing the typical needle-like morphology of ANC [26]. The fibers also exhibit a large number of longitudinal grooves indicative of partial oxidation on the fiber surface resulting from the pyrolysis treatment.…”
Section: Influence Of Nanoceramic-plating On Surface Hydrophilicity O...mentioning
confidence: 99%